Creating a model of threats to Ukraine’s national critical infrastructure as a basis for ensuring its security and resilience - D. S. Melnyk (Bulletin of Kharkiv National University of Internal Affairs)
The article presents the current problems of protecting Ukraine’s critical infrastructure, current threats to its security and the need to organise proper counteraction under martial law. Threats to critical infrastructure include factors that can actually or potentially harm the stability of its operation, functionality, integrity, resilience or lead to its destruction.